1997
DOI: 10.1159/000139513
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Hypothalamic- Pituitary-Adrenocortical Activity by Serotonergic Agents in the Rat

Abstract: The effects of tandospirone, enciprazine, gepirone, buspirone (5-HT1A agents) and carvotroline (5-HT2) on hypothalamic-pituitary-adrenocortical activity (HPA) activity were studied. These drugs increased the plasma corticosterone levels in a dose-dependent manner. Their ED50 values were 3.8, 31.8, 3.1, 3.4 and 7.0 mg/kg, respectively. Drug effects peaked between 30 min and 1 h, and plasma corticosterone levels returned to control levels after 2 h. When the drugs were given in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In fact, when we initially reported that N/OFQ increases circulating ACTH and CORT concentrations in unstressed and mildly stressed rats (Devine et al, 2001), we reconciled our hormonal findings with the published behavioral data (Jenck et al, 1997;Griebel et al, 1999) on the basis that a variety of drugs that are anxiolytic can also increase circulating CORT concentrations in unstressed or mildly stressed rats (Ellis, 1966;Kakihana et al, 1968;Marc and Morselli, 1969;Tabakoff et al, 1978;Rivier et al, 1984;Matheson et al, 1988Matheson et al, , 1997ade Boer et al, 1991). However, the current findings indicate that the behavioral and hormonal effects of N/OFQ resemble the effects of drugs like FG 7142 File, 1985, 1986), yohimbine (Smythe et al, 1983;Suemaru et al, 1989), amphetamine (Knych and Eisenberg, 1979;, and caffeine (Spindel et al, 1983;Fall of which are anxiogenic in neophobic tests of anxiety, and all of which elevate circulating ACTH and/or CORT concentrations after acute administration.…”
Section: Anxiogenic Action Of N/ofqsupporting
confidence: 52%
“…In fact, when we initially reported that N/OFQ increases circulating ACTH and CORT concentrations in unstressed and mildly stressed rats (Devine et al, 2001), we reconciled our hormonal findings with the published behavioral data (Jenck et al, 1997;Griebel et al, 1999) on the basis that a variety of drugs that are anxiolytic can also increase circulating CORT concentrations in unstressed or mildly stressed rats (Ellis, 1966;Kakihana et al, 1968;Marc and Morselli, 1969;Tabakoff et al, 1978;Rivier et al, 1984;Matheson et al, 1988Matheson et al, , 1997ade Boer et al, 1991). However, the current findings indicate that the behavioral and hormonal effects of N/OFQ resemble the effects of drugs like FG 7142 File, 1985, 1986), yohimbine (Smythe et al, 1983;Suemaru et al, 1989), amphetamine (Knych and Eisenberg, 1979;, and caffeine (Spindel et al, 1983;Fall of which are anxiogenic in neophobic tests of anxiety, and all of which elevate circulating ACTH and/or CORT concentrations after acute administration.…”
Section: Anxiogenic Action Of N/ofqsupporting
confidence: 52%